Treatment of Retained DJ(neglected DJ) in AL-Anbar Government, A Postconfict Study (Medico Legal Update, 2020)
Double J ureteral stents have been used to relieve or improve drainage in cases of ureteric obstructionfrom any causes (intrinsic or extrinsic). These forgotten or retained ureteral stents could lead to manycomplications. The objective of the paper is to assess the methods that used for treatment of neglecteddouble Jamong displaced persons. Across section study was done, 28 patients with neglected double J stentwere chosen from urology departments in Al-Ramadi & Al-Fallujah teaching hospitals. Result: Out of total(28) , 20 (71.4%) were males while females were 8 (28.6%) of the sample. The indication of insertionvaried between 13 (46.4% ) patients after Ureterorenoscopy procedure for ureteric stones (10 males & 3females ) and five (17.9% ) patients due to traumatic causes , four (14.3%) patients due to pyelolithotomy, three (10.7%) patients PNL for removal of renal stone. The complications rare which ranged from feverpostoperatively in nine patients (32.1%), two patients (7.1%) suffered from ureteric injury thatmandatedouble J insertion , three patients (10.7%) required more than two sessions to clear the ureter & remove ofretained double J.